2018
DOI: 10.1080/00325899.2017.1423200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of powder oxygen content on the microstructure and properties of Co–Cr dental alloys fabricated by selective laser melting

Abstract: A high oxygen content can lead to metallurgical defects such as holes and microcracks in the products of selective laser melting (SLM) that significantly reduce the density and mechanical properties of a denture. In this study, a batch of a Co-Cr alloy powder was subjected to forced oxidation. SLM was used to prepare specimens from the powder before and after the treatment for the performance tests. The results showed that Co-Cr alloy powders with oxygen contents 184 and 616 ppm could both achieve good shaping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It should be noted that the hardness of all the coatings is significantly higher than the substrate (193 Hv). Hardness values of these electrodeposits are also higher than those of bulk and sprayed films of Co-Cr-Mo alloys reported in other research works [2,[19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…It should be noted that the hardness of all the coatings is significantly higher than the substrate (193 Hv). Hardness values of these electrodeposits are also higher than those of bulk and sprayed films of Co-Cr-Mo alloys reported in other research works [2,[19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 50%
“…The Co–Cr alloys have a wide range of applications in different industries due to their good corrosion and wear resistance, along with suitable biocompatibility [1-3]. The Co–Cr electrodeposits can be an economic alternative for these expensive alloys [2-4]. These coatings are also a suitable substitute for hard chromium films [3,5-8].…”
Section: Introductionmentioning
confidence: 99%
“…Repeated re-use of powders through PBF processes can be tolerated, though it is common to observe an increase in oxygen content with recycling. Whilst this may reduce ductility, it has been shown that even CoCr powder subjected to deliberate oxidation still produced material within the required standard for cast F75 alloy [224].…”
Section: Defect Prevention and Fatigue Behaviourmentioning
confidence: 99%
“…However, they are complex and susceptible to being contaminated by impurities, and result in high generation of toxic gases. 16,17 In addition, there were also reported investigations on molten salt electroplating for preparing ZrB 2 coatings, which can produce coatings with good quality with strict process parameters. 18,19 Thus there are still many problems to be solved for the preparation process of ZrB 2 coatings.…”
Section: Introductionmentioning
confidence: 99%
“…CVD approaches allow accurate control of the composition and structure of the coating by regulating the deposition process. However, they are complex and susceptible to being contaminated by impurities, and result in high generation of toxic gases 16,17 . In addition, there were also reported investigations on molten salt electroplating for preparing ZrB 2 coatings, which can produce coatings with good quality with strict process parameters 18,19 .…”
Section: Introductionmentioning
confidence: 99%